STUDY OF GASEOUS PRODUCTS OF PLANT WASTE PYROLYSIS - Kholmanskikh, A.; Kozhevnikov, Y.; Chirkov, V.; Sorokina, E. (Енергетика і автоматика, 2016)
Analysis of gases from the fast pyrolysis of cellulose. It has been established that they contain a sufficient amount of light hydrocarbons, suitable for use as a renewable energy source. It is advisable to add reactors cheaper inert gas and metal in the form of chips or pieces of wire.